Psychosocial Effects of the COVID-19 Pandemic and Mental Health among LGBTQ+ Young Adults: A Cross-Cultural Comparison across Six Nations. Issue 4 (21st March 2021) - Gato, Jorge; Barrientos, Jaime; Tasker, Fiona; Miscioscia, Marina; Cerqueira-Santos, Elder; Malmquist, Anna; Seabra, Daniel; Leal, Daniela; Houghton, Marie; Poli, Mikael; Gubello, Alessio; Ramos, Mozer de Miranda; et al.
ABSTRACT: Across the world, people have seen their lives interrupted by the COVID-19 pandemic. Using an online survey, we explored how the psychosocial effects of the pandemic affected the mental health of LGBTQ+ young adults who were confined with their parents during the lockdown period ( N = 1, 934), from six countries: Portugal, UK, Italy, Brazil, Chile, and Sweden. South American participants experienced more negative psychosocial effects of the pandemic. Depression and anxiety were higher among participants who were younger, not working, living in Europe and who reported feeling more emotionally affected by the pandemic, uncomfortable at home, or isolated from non-LGBTQ friends. Not attending higher education predicted depression while not being totally confined at home, residing habitually with parents, and fearing more future infection predicted anxiety. LGBTQ+ community groups, as well as health and educational services should remain particularly attentive to the needs of LGBTQ+ young adults during health crises.